Investigating the Mediating Role of Resilience in the Relationship Between Cognitive Emotion Regulation and the Quality of Life of Young Couples - Moslemi, Maryam; Hatami, Mohammad (International Journal of Education and Cognitive Sciences, 2022)
Purpose: Research indicates that resilience is considered an important factor among several at-risk groups and plays a crucial mediating role in the manifestation of numerous psychological disorders. The present study aims to investigate the mediating role of resilience in the relationship between cognitive emotion regulation and the quality of life of young couples. Methodology: The research method was correlational. The study population included all married students at Shahroud Islamic Azad University, with 45 couples selected through convenience sampling. Subsequently, participants completed the Connor-Davidson Resilience Scale (2003), the Garnefski, Kraaij, and Spinhoven Cognitive Emotion Regulation Questionnaire (2001), and the World Health Organization Quality of Life questionnaire (1996). Data were analyzed using Pearson correlation coefficient and multiple regression statistical methods. Findings: The findings of this study indicate that cognitive emotion regulation and quality of life are significant positive predictors of resilience. Resilience plays a significant mediating role in the relationship between cognitive emotion regulation and the quality of life of couples. Conclusion: Given the results, it can be said that the strategies couples employ to regulate their emotions can be a very important factor in determining their resilience, which in turn enhances the quality of life. Strengthening positive cognitive emotion regulation strategies can be considered as a goal for the foundation of resilience interventions and educational programs.